Oral Submucous Fibrosis: A Review on Biomarkers, Pathogenic Mechanisms, and Treatments - Shen, Yen-Wen (Int J Mol Sci, 2020)
Oral submucous fibrosis (OSF) is a collagen deposition disorder that affects a patient’s oral function and quality of life. It may also potentially transform into malignancy. This review summarizes the risk factors, pathogenic mechanisms, and treatments of OSF based on clinical and bio-molecular evidence. Betel nut chewing is a major risk factor that causes OSF in Asia. However, no direct evidence of arecoline-induced carcinogenesis has been found in animal models. Despite identification of numerous biomarkers of OSF lesions and conducting trials with different drug combinations, clinicians still adopt conservative treatments that primarily focus on relieving the symptoms of OSF. Treatments focus on reducing inflammation and improving mouth opening to improve a patient’s quality of life. In conclusion, high-quality clinical studies are needed to aid clinicians in developing and applying molecular biomarkers as well as standard treatment guidelines.